ProCAss: An intelligent assessment for computer programming corpus - Zen, Kartinah; Tarmizi, Seleviawati; A.I, Dayang Nurfatimah; Din, Inson; Chua, Sui Soon (2005)
Electronic assessment (e-assessment) becomes more popular in educational tools especially in e-learning environment.This is because it has some advantages such as reducing the staffs needed for assessment tasks, automated marking is not prone to human error and it gives instant feedback to the students.However, the e-assessment existed only more on assessing essays and lack of implementation in assessing computer program in computer science environment [Haley, et.al, 2003]. This paper will briefly describe on the techniques that have been used to implement e-assessment for essays such as Project Essay Grade (PEG), E-rater, Intelligent Essay Assessor (IEA) and Latent Semantic Analysis (LSA).Mainly, the discussion will concentrate on LSA to build the eassessment for computer programming corpus.One great advantage of LSA over the others is its ability to make absolute relative comparisons, where set of documents can be compared to each other, or to an answer schema.Another reason is the computer program produces programs in a subset of English-like words, a bit similar to an essay [Haley, et.al, 2003].This paper will propose system design integrated with LSA method to assess student’s programming assignments. Then, the ability of LSA algorithm in grading computer program corpus will be evaluated.The grading process will not limited on certain programming languages, but on any programming languages.